The difference of acrylic resin residual monomer levels with various polymerization method - Sherman Salim (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: After polymerization process, heat cured acrylic resin denture base actually still contains residual monomers that can become potential irritants later in oral cavity. Polymerization process is essential to obtain acrylic resin which can meet the requirements of the biocompatible and good physical properties. To meet the requirements, there are several methods of polymerization process used. Purpose: The purpose of this study was to determine the differences of the residual monomer levels of acrylic resin processed by various polymerization methods. Methods: Acrylic resin powder and liquid were mixed based on the rules of factory, and sample was made with size of 30 mm × 50 mm × 3 mm and then polymerized by using microwave at 70° C for 24 hours based on the methods of Japan Industrial Standard (JIS). Each group of samples was cut with weight of ± 0.2 g, dissolved in 5 ml of methyl ethyl ketone in test tubes, and then stored at ± 5° C for four days. Residual monomer level was conducted by using gas chromatograph mass spectrometer. Data obtained were then analyzed by using One-Way ANOVA test with p < 0.05. Results: After the level of polymerizing residual monomer with JIS method was compared to that at 70° C for 24 hours using microwave, it is known that there were significant differences (p < 0.05). Conclusion: The highest level of residual monomer of acrylic resin was that polymerized at 70° C for 24 hours.Latar belakang: Basis gigi tiruan yang berbahan dasar resin akrilik jenis heat cured setelah proses polimerisasi selesai masih mengandung monomer sisa yang berpotensi sebagai bahan iritan dalam rongga mulut. Proses polimerisasi sangat penting untuk mendapatkan resin akrilik yang memenuhi persyaratan biokompatibilitas dan fisik yang baik. Untuk persyaratan tersebut digunakan berbagai macam proses polimerisasi. Tujuan: Penelitian ini bertujuan untuk menentukan kadar monomer sisa resin akrilik yang diproses dengan metode polimerisasi berbeda menggunakan gas chromatograph mass spectrometer. Metode: Bubuk dan cairan resin akrilik dicampur sesuai aturan pabrik dan sampel dibuat berukuran 30 mm × 50 mm × 3 mm dipolimerisasi berdasarkan metode Japan Industrial Standard (JIS), suhu 70° C selama 24 jam, dan microwave. Setiap kelompok sampel dipotong seberat ± 0,2 gram dilarutkan 5 ml dalam metil etil keton pada tabung uji dan disimpan suhu ± 5° C selama empat hari, dilakukan analisis kadar monomer sisa dengan gas chromatograph mass spectrometer. Data yang diperoleh dianalis ANOVA satu arah dengan nilai p < 0,05. Hasil: Kadar monomer sisa resin akrilik yang berpolimerisasi metode JIS dibandingkan polimerisasi suhu 70° C selama 24 jam dan microwave terdapat perbedaan bermakna (p < 0,05). Kesimpulan: Kadar monomer sisa paling tinggi pada resin akrilik yang dipolimerisasi suhu 70° C selama 24 jam.